Analysis of Calcium (Ca) and Potassium (K) Contents in Tin Fruits (Ficus carica Linn) - Hamzah, Abdul; Aminah, Sitti; Said, Irwan; Nurmayanti, Yuli (Jurnal Akademika Kimia, 2023)
Tin Fruits (Ficus carica Linn) are typical Middle Eastern plants that have been cultivated in Indonesia. Tin fruits are rich in minerals, especially calcium and potassium. In addition, they also contain benzaldehyde which is beneficial against cancer cells. This study aimed to determine the concentrations of calcium and potassium contained in tin fruits. Determination of calcium and potassium contents using an atomic absorption spectrophotometer (AAS). The results showed an analysis of the water content of the sample obtained was 89.065 %, ash content was 1.0165 % and biomass content was 9.9185 %. While the analysis of calcium contents at a wavelength of 422.7 nm and potassium at a wavelength of 766.5 nm respectively obtained that an average yield of calcium was 354.97 mg/100g and 752.68 mg/100g for potassium. The results of this study are expected to be able to attract the interest of the community to cultivate tin fruits, especially in Central Sulawesi.